2023
DOI: 10.1186/s12879-023-08275-z
|View full text |Cite
|
Sign up to set email alerts
|

Circulating mid-regional proadrenomedullin is a predictor of mortality in patients with COVID-19: a systematic review and meta-analysis

Abstract: Background Although there is increasing understanding of the changes in the laboratory parameters of Coronavirus disease 2019 (COVID-19), the correlation between circulating Mid-regional Proadrenomedullin (MR-proADM) and mortality of patients with COVID-19 is not fully understood. In this study, we conducted a systematic review and meta-analysis to evaluate the prognostic value of MR-proADM in patients with COVID-19. Methods The PubMed, Embase, Web… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 90 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…Wang et al [53], in a comprehensive meta-analysis, compared MR-proADM concentrations between two groups of COVID-19 patients, survivors and non-survivors, with a primary emphasis on mortality as the endpoint. The study confirmed a notable disparity in MR-proADM levels between the two patient groups.…”
Section: Impact Of Mr-proadm On Mortality In Covid-19mentioning
confidence: 99%
“…Wang et al [53], in a comprehensive meta-analysis, compared MR-proADM concentrations between two groups of COVID-19 patients, survivors and non-survivors, with a primary emphasis on mortality as the endpoint. The study confirmed a notable disparity in MR-proADM levels between the two patient groups.…”
Section: Impact Of Mr-proadm On Mortality In Covid-19mentioning
confidence: 99%
“…There are distinct temporal trends in selected routine laboratory parameters between survivors and non-survivors with severe COVID-19 admitted to the intensive care unit (ICU), indicating their importance in the prognosis of clinical outcome [1]. Recent investigations revealed new diagnostic biomarkers of the disease, such as mid-regional pro-adrenomedullin [2,3], monocyte distribution width [4,5], electrolyte imbalances [6], pentameric C-reactive protein [7], and pentraxin-3 [8,9]. Also, several recent studies provided insights on adipokines (chemerin, adiponectin, leptin, apelin, visfatin, resistin, galectin-3) as diagnostic and prognostic markers for the severity of COVID-19 [10,11].…”
Section: Introductionmentioning
confidence: 99%